2018
DOI: 10.1016/j.neuroimage.2017.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Brain correlates of constituent structure in sign language comprehension

Abstract: During sentence processing, areas of the left superior temporal sulcus, inferior frontal gyrus and left basal ganglia exhibit a systematic increase in brain activity as a function of constituent size, suggesting their involvement in the computation of syntactic and semantic structures. Here, we asked whether these areas play a universal role in language and therefore contribute to the processing of non-spoken sign language. Congenitally deaf adults who acquired French sign language as a first language and writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…The participants' task was to respond to occasional probe sentences that explicitly asked them to press a button. Moreno et al (2018) found that reading sentences compared to lists of words engaged a strongly left-lateralized network for deaf readers, including middle and inferior frontal cortices and superior and middle temporal cortices, replicating the results found for hearing readers (Pallier et al, 2011). Consistent with Hirshorn et al (2014), neural activation was also observed in right superior temporal cortex (including auditory regions) for reading sentences compared to word lists.…”
Section: <1> Sentence Readingsupporting
confidence: 82%
See 2 more Smart Citations
“…The participants' task was to respond to occasional probe sentences that explicitly asked them to press a button. Moreno et al (2018) found that reading sentences compared to lists of words engaged a strongly left-lateralized network for deaf readers, including middle and inferior frontal cortices and superior and middle temporal cortices, replicating the results found for hearing readers (Pallier et al, 2011). Consistent with Hirshorn et al (2014), neural activation was also observed in right superior temporal cortex (including auditory regions) for reading sentences compared to word lists.…”
Section: <1> Sentence Readingsupporting
confidence: 82%
“…Emmorey et al (2016) found that activation within right inferior frontal cortex was positively associated with reading skill when deaf readers made a semantic decision to words. At the sentence level, Moreno et al (2018) found that activation in right (and left) superior temporal cortex (including auditory regions) was positively correlated with lexical ability for deaf readers. Hirshorn et al (2014) also found greater bilateral activation in auditory regions when deaf readers (signers and non-signers) comprehended sentences compared to their reading-matched hearing peers.…”
Section: The Neurobiology Of Reading 27mentioning
confidence: 98%
See 1 more Smart Citation
“…Cortical structures that are deprived of their normal sensory input may become responsive to the stimulation of adjacent receptors, a process that is generally known as cross-modal plasticity or cross-modal reorganization [ 1 ]. In human brain imaging studies, there is growing evidence showing that, in early bilaterally deaf adults, the superior temporal cortex (STC) may experience cross-modal recruitment of different visual inputs, such as visual motion [ 2 8 ], biological motion [ 9 11 ], sign language [ 11 19 ], and silent speech reading [ 15 , 20 23 ]. Animal models have also confirmed the dystrophic change that occurs when the auditory cortex fails to develop typically due to the absence of auditory input [ 24 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visual-related responses in the STC of deaf subjects could result from long-term auditory deprivation (e.g., missing auditory sensory input) but could also be caused by other dynamic cognitive functions (e.g., sign language learning) [ 1 , 12 , 16 , 19 , 29 , 30 ]. In the previous studies, STC activity was found to positively correlate with the duration of deafness or the age at cochlear implantation [ 2 , 18 , 31 35 ], suggesting that functional reorganization was likely to take place in the auditory cortex over a considerable period of time.…”
Section: Introductionmentioning
confidence: 99%